The Roles and Profile of School Nurses in Bahrain - Dr Fatin Hasani. RN (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Hospitals, clinics, nursing homes, and health centres are the traditional places where nurses work, but nurses have recently started working in new areas such as government and private schools, and they play a critical role in the educational setting for achieving better health outcomes. In order to better understand these roles, this study aimed to create a profile of school nurses in Bahrain and explore their roles. The researchers adopted a mixed methodology involving quantitative and qualitative methods of data collection. The study established several factors impacting roles of school nurses in Bahrain, and both government and private school nurses reported aforementioned elements. The study concluded that creative solutions should be introduced to improve working conditions for nurses in schools.